Professional ASP data access (Wrox, 2000)
With the advent of Universal Data Access from Microsoft, we see data being stored in a variety of places - mail systems, directory services, Internet services and so on. To build great Web applications you need to drive your site with data, in whatever form it takes. This means data access and manipulation on the server to bring dynamic content to the end user. A well-constructed site will not only access data, but also manage it efficiently. This is imperative to ensure users perceive the site well and that it scales to cope with increased numbers of users.